A Mineralogical and petrological investigation of the Platreef on Drenthe 778 LR, northwest of Potgietersrus - Von Gruenewaldt, G. (Gerhard), 1942- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1982.